2015
DOI: 10.1186/s13578-015-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of aberrant DNA methylation in Apcmin/+ mice with the epithelial-mesenchymal transition and Wnt/β-catenin pathways: genome-wide analysis using MeDIP-seq

Abstract: BackgroundAberrant DNA methylation at the 5-carbon on cytosine residues (5mC) in CpG dinucleotides is probably the most extensively characterized epigenetic modification in colon cancer. It has been suggested that the loss of adenomatous polyposis coli (APC) function initiates tumorigenesis and that additional genetic and epigenetic events are involved in colon cancer progression. We aimed to study the genome-wide DNA methylation profiles of intestinal tumorigenesis in Apcmin/+ mice.ResultsMethylated DNA immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Thus, our data do not support methylation of the APC promoter as a ‘second hit' in one-hit APC tumours. This agrees with several recently published studies showing that promoter methylation in APC plays an insignificant role in substituting for truncating mutations 44 45 . Collectively, we have identified a significant number of tumours harbouring one-hit APC mutations, many of which retained WNT activation that could not be explained by a few possible ‘second-hit' mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, our data do not support methylation of the APC promoter as a ‘second hit' in one-hit APC tumours. This agrees with several recently published studies showing that promoter methylation in APC plays an insignificant role in substituting for truncating mutations 44 45 . Collectively, we have identified a significant number of tumours harbouring one-hit APC mutations, many of which retained WNT activation that could not be explained by a few possible ‘second-hit' mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous studies using DSS‐induced colitis model showed hypermethylation of the promoter region of sfrp1 and dkk3 , suggesting their protective role against colon inflammation . Consistently, sfrp1 and dkk3 were hypermethylated in human CRC and in Apc Min/+ mice . Overexpression of DKK3 suppressed proliferation and invasion, induced apoptosis, and reduced the β‐catenin accumulation in colon cancer cells .…”
Section: Discussionmentioning
confidence: 54%
“…15 Consistently, sfrp1 and dkk3 were hypermethylated in human CRC 25,26 and in Apc Min/1 mice. 27 Overexpression of DKK3 suppressed proliferation and invasion, induced apoptosis, and reduced the b-catenin accumulation in colon cancer cells. 28 In addition, SOCS1 is a suppressor of cytokine signaling, and it has been reported to inhibit the reactive oxygen species (ROS)-induced epithelial-mesenchymal transition of colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found no evidence of reduced 5mC levels in Tumours relative to WT or NAdj samples. Recent genomewide analyses have indeed shown equal gains and losses of methylation at regions with differential methylation between Apc Min/+ tumours and normal tissue 38 . In addition, we have previously shown that 5mC levels are progressively reduced from normal tissue to adenoma to adenocarcinoma 37 , suggesting that marked genome-wide changes observed with malignant progression have not taken place in the more benign Apc Min/+ intraepithelial adenomas.…”
Section: Discussionmentioning
confidence: 99%